Family experiences before a child's diagnosis with a rare life-limiting condition: findings from a national mixed-method study. (24th May 2012) - Malcolm, C; Hain, R; Gibson, F; Adams, S; Anderson, G; Morley, A; Forbat, L
Abstract : Aims: This paper focuses on families where a child is diagnosed with a rare life-limiting condition during the early years of life. We describe how families manage their child's symptoms, and the associated psychosocial impact, before the certainty of a diagnosis is reached. Methods: This paper reports on the qualitative component of a mixed-method study. Twenty-six children and their families were recruited from children's hospices across the UK. All children had a diagnosis of either Mucopolysaccharide disease (MPS) or Batten disease. These rare life-limiting conditions are characterised by progressive and permanent loss of physical and cognitive function. Using Grounded Theory as the guiding methodology, parents, siblings and practitioners were interviewed to document the symptom profile and family experiences of caring for a child with a rare life-limiting condition. Results: The early years of supporting a child with MPS or Batten disease, before a firm diagnosis is made, are fraught with uncertainty. Parents struggle to manage the psychosocial impact of these rare conditions which have highly visible symptoms (such as aggression and hyperactivity). Although parents begin to suspect that something is not quite right with their child from an early age, the rarity of these conditions precludes securing a rapid differential diagnosis. Between first noticing symptoms to the point of diagnosis parents often struggled with how friends, family and members of the public responded to them and, in particular, how their identity as a parent was challenged. During this time, parents report receiving little professional support, despite numerous contacts with multiple practitioners. Following diagnosis the narrative arc changed. Many parents began to feel more reassured that their parenting was not to blame for on-going physical or behavioural difficulties. Conclusions: Improved supports are required for parents with young children with complex symptoms in the time before a diagnosis is reached. Practitioners involved in routine developmental monitoring, (health visitors and GPs) and symptom-specific specialists, could support parents to keep a symptom diary to routinely document symptoms. Recording troubling and unexplained symptoms will increase parental self-efficacy and provide clinicians with detailed symptom descriptions which may not be apparent during consultations.